Care and outcomes of Canadian children hospitalised with periorbital and orbital cellulitis: protocol for a multicentre, retrospective cohort study. Issue 12 (22nd December 2019) - Gill, Peter J; Parkin, Patricia C; Begum, Nurshad; Drouin, Olivier; Foulds, Jessica; Pound, Catherine; Quet, Julie; Vomiero, Gemma; Wahi, Gita; Sakran, Mahmoud; Kozlowski, Natascha; Bayliss, Ann; et al.
Abstract : Introduction: Skin and soft tissue infections of the eye can be classified based on anatomic location as either anterior to the orbital septum (ie, periorbital cellulitis) or posterior to the orbital septum (ie, orbital cellulitis). These two conditions are often considered together in hospitalised children as clinical differentiation is difficult, especially in young children. Prior studies have identified variation in management of hospitalised children with orbital cellulitis; however, they have been limited either as single centre studies or by the use of administrative data which lacks clinical details important for interpreting variation in care. We aim to describe the care and outcomes of Canadian children hospitalised with periorbital and orbital cellulitis. Method and analysis: This is a multisite retrospective cohort study including previously healthy children aged 2 months to 18 years admitted to hospital with periorbital or orbital cellulitis from 2009 to 2018. Clinical data from medical records from multiple Canadian hospitals will be collected, including community and academic centres. Demographic characteristics and study outcomes will be summarised using descriptive statistics, including diagnostic testing, antibiotic therapy, adjunctive therapy, surgical intervention and clinical outcomes. Variation will be described and evaluated using χ² test or Kruskal-Wallis test. Generalised linear mixed models will be used to identify predictors of surgical intervention and longer length of stay. Ethics and dissemination: Approval of the study by the Research Ethics Board at each participating site has been obtained prior to data extraction. Study results will be disseminated by presentations at national and international meetings and by publications in high impact open access journals. By identifying important differences in management and outcomes by each hospital, the results will identify areas where care can be improved, practice standardised, unnecessary diagnostic imaging reduced, pharmacotherapy rationalised and where trials are needed.